A reliable solution of path optimisation in LEACH protocol by implementing trust-based neural network. (2019) - ,; Pahuja, G.L.
The mobile ad hoc networks (MANETs) are an infrastructure-less network consisting of a collection of wireless mobile self-directed nodes that communicate with each other without using any centralised authority. MANET is a network in which large numbers of powered mobile nodes are used but the network has always suffered from limited power resource problem due to the mobility nature of nodes. So, in the proposed work we have focused on the least power utilisation by developing an artificial intelligence-based enhanced leach (E-LEACH) routing protocol and designed a hybrid neuro-soft computing technique for the problem. The proposed solution is effective in solving the power resource problem and trust management in MANETs. This work has found a reliable solution to the route optimisation problem in E-LEACH protocol. The whole framework has been titled as energy efficient neuro genetic leach (EENG LEACH). Various performance metrics as throughput, bit error rate (BER), packet delivery ratio (PDR), congestion and energy consumption have been calculated to authenticate the proposed method.